Improvements in the Acylation of 3-Methylindole Using Amberlyst-15 - Vargas, Darío A.; Méndez, Leticia J.; Cánepa, Alicia S. (Letters in Organic Chemistry, 2020)
A simple and efficient methodology for Friedel-Crafts acylation of 3-methylindole using Amberlyst 15 resin as catalyst is described. This methodology shows good selectivity towards the formation of the products of 2-acylation, (3-methyl-1H-indol-2-yl)ketones. Several advantages can be ascribed to Amberlyst 15, among them; are the ease of handling, quick separation from the reaction mixture and minimum or no production of the chemical residues that must be eliminated. Besides, the catalyst can be easily recycled and reused with a minimal loss in activity through 6 reaction cycles. The catalyst was characterized by FT-IR spectroscopy and superficial acidity.
Keywords: Acylation reaction